Dissolution testing of prolonged-release tablets using experimental design approach - Blagica Manchevska; Filip Smilcevski; Maja H Gigovska; Packa Antovska; Sonja Ugarkovic (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2020)
Dissolution testing is an essential tool in the pharmaceutical industry and is used in formulation and process development, in monitoring of the manufacturing process, as a quality control test, to predict the in vivo performance. The purpose of this study is to evaluate the behaviour of the test and reference products using conventional dissolution apparatus basket and paddle, with tendency to evaluate the dependence of the in vitro dissolution of the dissolution test conditions (dissolution apparatus, medium, agitation, pH). Experimental design (ED) approach has been employed for assessment of the discriminatory properties of different dissolution conditions. The responses statistically evaluated were: f2 similarity factor and the difference in the dissolution rate between the test and reference product, expressed in percentage, at every time point. Furthermore, this study focusses on developing a statistically reliable mathematical model for predicting discriminatory experimental conditions.